Analytical Study of Antipsychotic Use in Schizophrenia Patients - Sinta wahyuni; Yulistiani; Indra Zeth; Josephine P (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Schizophrenia is a chronic mental disorder that affects thought processes, emotions, perceptions, and behavior. Antipsychotics are divided into first-generation (FGA) and second-generation (SGA) as the main therapy. Objective: To analyze the profile of antipsychotic use in hospitalized schizophrenia patients, including type, dose, route, frequency, and combination patterns. Methods: A retrospective observational study at Menur Mental Hospital Surabaya from July to September 2023 on 66 hospitalized schizophrenia patients. Data were analyzed descriptively. Results: The use of SGAs was more dominant than FGAs. The most common SGAs were clozapine 25 mg and risperidone 3 mg oral. The most common FGAs were trifluoperazine 5 mg and chlorpromazine 100 mg oral. The most common combination pattern was risperidone + clozapine. Conclusion: The pattern of antipsychotic use was dominated by the combination of risperidone and clozapine, reflecting the complexity of schizophrenia management that requires an individual approach.